Inter-City Inter-Provincial Transportation Service at The Kalideres Bus-Station at The 2019-2021 - Intan Handayani; Bhakti Nur Avianto (Publikasi Indonesia, 2023)
This study aims to determine public services in the field of Intercity and Interprovincial (AKAP) Bus transportation in Terminal Kalideres between 2017-2019, considering that Kalideres Terminal is the largest in Jakarta with more than 5,000 passengers. This large number results in still not optimal service functions managed by the DKI Jakarta Provincial Transportation Agency. The research method used a qualitative approach to find out more about public services in the field of transportation involving informants from the management and passengers. The results showed that with the rapid development of cities, human activities are increasingly diverse, so we need a system that regulates the transportation system in Indonesia. The impact that arises is the increasing intensity of human movement as labor and goods as production materials. The factor of means and transportation greatly affects the smooth mobility of passengers and goods. Therefore, in addition to infrastructure factors, service factors also have an important role. This study used the snowball sampling technique, which determined informants based on previous informants without determining the exact number by digging up information related to the required research topic. This paper is intended to improve the quality of service and satisfaction of Kalideres bus-station service users.